Illegitimacy of penalizing incestuous relations and the offspring issue - Maciej Para (Acta Universitatis Lodziensis Folia Iuridica, 2018)
The paper proposes a thesis that penalization of incestuous relations is illegitimate on the grounds of inconsistency it creates in the legal system. On one hand, the legislator has to be neutral in its worldview and therefore should not create laws based on its own or even shared by some people cultural taboos – and if it were to, it should do it also in other cases, which may lead to penalizing, for example, cases of adultery in marriage. On the other hand – if the base of penalizing incestuous relations is a eugenic one, then in order to maintain coherency of the legal system, relations between people suffering from severe genetic and inherited diseases should also be penalized. After all, they also pose a danger to the gene pool. Thus, it should be stated that penalizing incestuous relationships – at least in the way currently proposed, without adjusting the other legal system is illegitimate.